OPTIMASI PRODUKSI PROTEIN SEL TUNGGAL DARI BAGASE TERHIDROLISA DENGAN FERMENTASI OLEH SACCAROMYCES CEREVICEAE - Isti Pudjihastuti; Margaretha T S; Wahyuningsih Wahyuningsih; Edy Supriyo (METANA, 2014)
The Came pulp (bagase) were main contained cellulose, through process delignification and hidrolized can be used to growting sacaromyces cereviceae yeast as fermented media, so can produced biomass microbial as known as single cell protein (SCP).Design experiment was random block with treatment nutrient added as long as fermented process. The measured parameter were protein contained in microbial biomass with Kehjdahl method. Optimum result were formed to 8 days fermentation and nutrient added (NH4)2SO4:1 gr,MgSO47H2O : 0,5 gr, molase (tetes) 20% : 2 ml to media 50 gr. Key word: bagase, Saccaromyces Cereviceae,SCP